Engendering intergovernmental transfers: Is there a case for gender-sensitive horizontal fiscal equalization? - Abhishek Anand; Lekha S. Chakraborty (Levy Economics Institute of Bard College, 2016)
This paper seeks to evaluate whether a gender-sensitive formula for the inter se devolution of union taxes to the states makes the process more progressive. We have used the state-specific child sex ratio (the number of females per thousand males in the age group 0-6 years) as one of the criteria for the tax devolution. The composite devolution formula as constructed provides maximum rewards to the state with the most favorable child-sex ratio, and the rewards progressively decline along with the declining sex ratio. In this formulation, the state with the most unfavorable child-sex ratio is penalized the most in terms of its share in the horizontal devolution. It is observed that the inclusion of gender criteria makes the intergovernmental fiscal transfers formula more equitable across states. This is not surprising given the monotonic decline in the sex ratio in some of the most high-income states in India.
Keywords: E62; E63; 330; Fiscal Devolution; Gender; Equity; Intergovernmental Transfers